Internet traffic and firm performance in big-ticket sectors: there are two sides of the coin - Lubov Spitsina; Andrey Kretinin; Vladislav Spitsin (Retos: Revista de Ciencias de la Administración y Economía, 2022)
The importance of well-established and customer-friendly firms’ websites has increased in the context of the digitalization of the economy. The COVID-19 pandemic has become a new driver for the development of Internet communications between manufacturers and consumers. This article explores the relationship between the Internet traffic of companies’ websites of and their sales volumes and profitability. We apply panel data regression analysis and model of Prais–Winsten regression with panel standard error adjustment, which provides conservative and reliable estimates. In the sample of 268 observations drawn from 67 Russian firms operating in the big-ticket industries of car manufacturing and real estate development during the period of 2017- 2022 characterized by a major exogenous shock, we demonstrate that internet traffic exerts a positive effect on firm sales. At the same time, this positive effect on sales is accompanied by a negative effect of internet traffic on firm profitability. The negative effect on profitability is particularly pronounced for younger firms that are likely to face severe resource constraints and can thus be said to sacrifice profitability to ensure sales. In such situation, application of cost-effective strategies may be critical for younger firms. Younger firms should pay particular attention to the contents of their websites to ensure that they provide enough adequate information that will help win the trust of new customers.